Peningkatan Kapasitas Pokdarwis Desa Sukajadi melalui Lokakarya dan Pelatihan Community based Tourism - Sarwititi Sarwoprasodjo; Pudji Muljono; Yeti Lis Purnamadewi; Ratih Kurnia Hidayati; Iis Mardiansyah; Alfianita Rakasiwi Putri; Leonita Arshinta Cinara (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2023)
The development of tourism villages in Bogor Regency, particularly in Sukajadi Village, Tamansari District, confronts various challenges, encompassing issues about establishing local tourism management institutions, small-scale business development, promotional strategies, product packaging, and environmental sustainability. These challenges are addressed through the implementation of the Community Partnership Empowerment (PKM) initiative within the framework of Community-Based Tourism (CBT) in collaboration with the Tourism Awareness Group (Sukajadi Village) as the partnering institution. The objectives of the PKM CBT endeavour are as follows: 1) To enhance tourism awareness among Sukajadi village residents; 2) To augment the capacity of the Pokdarwis institution in effectively managing the tourism potential of Sukajadi Village as a CBT destination; 3) To improve the proficiency in crafting promotional content for tourist attractions to reach individuals beyond Bogor Regency and City; and 4) To enhance the skills in packaging products of Small and Medium Enterprises (SMEs) to render them more appealing as flagship offerings. The conducted activities encompass 1) The execution of the CBT Development Workshop involving diverse representatives of community figures; 2) The House Charm Competition targeting the general public; 3) Training sessions on the Analysis of SME and Village Tourism Potential with the participation of Pokdarwis management and community figures and; and 4) Training on the packaging of tourism products for SMEs, coupled with the promotion of CBT to Pokdarwis management. The outcomes of this PKM initiative reveal an elevation in knowledge, attitudes, and competencies related to tourism management among Pokdarwis administrators. At the institutional level, PKM serves to enhance the planning capabilities of Pokdarwis in the development of community-based tourism and the promotion of tourism initiatives. This, in turn, is anticipated to positively impact the local community's income through CBT enterprises and foster a heightened awareness of tourism among the general public.